2015
DOI: 10.1016/j.biocon.2015.01.020
|View full text |Cite
|
Sign up to set email alerts
|

Natural regeneration of forest vegetation on legacy seismic lines in boreal habitats in Alberta’s oil sands region

Abstract: a b s t r a c tMapping of oil reserves involves the use of seismic lines (linear disturbances) to determine both their location and extent. Conventional clearing techniques for seismic assessment have left a legacy of linear disturbances that cause habitat fragmentation. Little is known, however, about how local and landscape factors affect natural regeneration patterns of trees and shrubs on seismic lines that facilitate mapping and future projections of regeneration patterns. To understand factors affecting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
132
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(146 citation statements)
references
References 29 publications
4
132
0
3
Order By: Relevance
“…Assuming that our study site is indicative of typical treed bog conditions, these findings can partially explain the lack of successful ecosystem recovery (i.e., restoration of ground surface, hydrological, and vegetation conditions comparable to predisturbance) along linear features within the western Canadian Boreal region. van Rensen et al () indicated that wetter (flooded) areas are less likely to establish new Sphagnum moss communities, an important genus in natural hummock formation. This suggests that LIS lines within our study site, and those in comparable disturbed peatlands, are highly unlikely to recover without the pursuit of active restoration designed to recreate suitable surface conditions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Assuming that our study site is indicative of typical treed bog conditions, these findings can partially explain the lack of successful ecosystem recovery (i.e., restoration of ground surface, hydrological, and vegetation conditions comparable to predisturbance) along linear features within the western Canadian Boreal region. van Rensen et al () indicated that wetter (flooded) areas are less likely to establish new Sphagnum moss communities, an important genus in natural hummock formation. This suggests that LIS lines within our study site, and those in comparable disturbed peatlands, are highly unlikely to recover without the pursuit of active restoration designed to recreate suitable surface conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Peatlands in the Canadian province of Alberta and elsewhere have been heavily disturbed by the construction of seismic lines for petroleum resource exploration (Pasher et al, ; Schneider & Dyer, ). Seismic lines can be extremely disruptive to low‐lying peatland ecosystems, often triggering persistent changes in environmental factors such as hydrology (van Rensen et al, ), which may have implications on GHG release rates. Seismic lines are not limited to Alberta, occurring within various other provinces and territories of Canada as well as in other regions such as Siberia (Scott, ; Williams et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In many instances, vegetation recovery on these lines is extremely slow (Schneider ), especially in wetter lowlands (van Rensen et al. ), which are important caribou habitats.…”
Section: Introductionmentioning
confidence: 99%
“…After a well has finished producing, the site is decommissioned and the land reclaimed to a more natural state, according to regulations outlined by Alberta's Environmental Protection and Enhancement Act [2]. However, rates of post-disturbance recovery have been found to vary considerably [3,4]. For example, Pinno and Hawkes [5] examined plant community structure derived PPCs for estimating vegetation characteristics include those shown by Guerra-Hernandez et al [34], Jensen and Mathews [35], and Wallace et al [36].…”
Section: Introductionmentioning
confidence: 99%